I' ve Seen Santa! - Bedford, David (Little Tiger Press, 2005)
It's Christmas Eve and Little Bear can't wait for Santa to deliver his presents. 'Santa will come just as soon as you go to sleep', Mummy Bear says. But Little Bear doesn't want to go to sleep. He wants to see Santa. Suddenly, glug, glug, glug! What's that noise? Is someone downstairs!
Keywords: Legends, Myths, Fables; General; Juvenile Fiction